SOSIALISASI NILAI ADAT DALIHAN NA TOLU PADA REMAJA BATAK DI PUNGUAN SILAU RAJA PEKANBARU - Mangari Manik; WE. Tinambunan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Dalihanna tolu is the essence of life Batak tribe. Indigenous values contained in this dalihan na tolu set any custom activity in the environment Batak. In dalihan na tolu human was same and there is no difference based on the layers in society. Dalihannatolu consists of sombamarhula-hula, elekmarboru, and manat mardongan tubu. To maintain ties with family at clan of Batak and maintain strength in the existing value in Dalihannatolu then in each clan in the Batak tribe has punguan. Seeing the condition of today's modern versatile and look at the condition of the city of Pekanbaru the existence of diverse ethnic cultures need to be preserved. To maintain the existence of indigenous cultural values, we need a process of socialization to the next generation by the family to his son who was a adolescent. This is to make the next generation to maintain essentially the culture and not be individuals who dalle.This study used a qualitative research method is descriptive presentation. Informants in this research is that there are families in PunguanSilau Raja and administrators Punguan Silau Raja as key informants using snowball techniques. Data collection techniques using participant observation, interviews and documentation.The results showed that the way of the process of socialization dalihannatolu that parents do to their children who have adolescent based SOR theory: process of teaching students about their own clan lineage and teachings in order to perform speech martutur good greetings and custom events Batak used as a medium of socialization dalihan natolu. Contributing factor in this process is active parental socialization in punguan and custom events as well as participatory socialization patterns. Inhibiting factor in the socialization process is that parents are not active in punguan and rarely follow the traditional events as well as the pattern of repressive socialization. The role of the socialization process are: improved knowledge of indigenous Batak and teens will receive a positive attitude towards the socialization process and the behavior of the running values dalihan natolu social at their life.Keywords: Socialization, Adolescent,Dalihan na Tolu, Dalle, SOR Theory